SAT0242 How good are the eular sjögren's syndrome disease activity index (ESSDAI), and EULAR sjögren's syndrome patients reported index (ESSPRI) in predicting health status in primary sjögren's syndrome?. (23rd January 2014) - Ng, W.-F.; Mitchell, S.; Lendrem, D.; Bowman, S.; Price, E.; Pease, C.; Emery, P.; Andrews, J.; Bombardieri, M.; Sutcliffe, N.; Pitzalis, C.; Lanyon, P.; et al.
Abstract : Background: Over the past 2 years, the EULAR Sjogren's syndrome study group have developed 2 new instruments, ESSDAI and ESSPRI to measure systemic disease activity and overall symptom burden. The ESSPRI also generates an EULAR sicca score (ESS) which measures the overall symptom of dryness. These instruments are designed to be used as standardised outcome measures for clinical studies and trials. Therefore it is useful to investigate how well these instruments predict the health status of patients with primary Sjogren's syndrome (PSS). EQ-5D is a generic instrument that measure health outcome, the value sets can be converted to Time Trade Off (TTO) values representing the time a patient would be willing to give up to be freed from a reduced health state. In this study, we examined the relationship between ESSDAI and ESSPRI and the TTO values derived from EQ-5D. Objectives: To evaluate the relationship between the two new instruments for the assessment of PSS (ESSDAI and ESSPRI) and health status of PSS patients. Methods: Data including ESSDAI, ESSPRI and EQ-5D were prospectively collected from 633 PSS patients who have participated in the UK PSS registry (UKPSSR) using a standardised pro forma as previously described (1). TTO values were derived from the UK reference data provided by EuroQoL (the developer of the EQ-5D instrument) which has been transformed so that the values range from -1 to 1, with 1 being the number of years in perfect health state, 0 being dead and negative values representing health states worse than being dead. The relationships between the derived TTO values based on the health state of the patients and ESSDAI, ESSPRI as well as ESS were determined. Results: The mean±SD TTO value of the PSS cohort was 0.624±0.301, with a range of -0.239 to 1. There were statistically significant correlations between TTO and ESSDAI, ESSPRI and ESS; TTO values decreased with increased ESSDAI, ESSPRI and ESS values (p<0.001 for all three). The strength of correlation was strongest with ESSPRI (R=-0.64), followed by ESS (R=-0.29) and ESSDAI (R=-0.15). Conclusions: The recently developed EULAR PSS outcome assessment tools, in particular the ESSPRI, are useful predictors of the health status of PSS patients. Other UKPSSR collaborators: Moots R, Chadravarty K, Gendi N, Hamburger J, Richards A, Rauz S, Mulherin D, Kitas GD, Lloyd M, Lawson C, Clunie G, Knight S, Symmons D, Carr A, Carrozzo M, Figuereido F, Macleod I, Tarn JR, Foggo H, Edgar S, Young-Min S, Field A, Kaye S, Mewar D, Akil M, Dasgupta B, Fedele S, Porter S, Li C, Hall F. References: Ng WF et al, Rheumatology, 2011;50:32-9. Disclosure of Interest: None Declared